Enzymatic synthesis of esters by chiral ionic liquids coated lipase from Candida rugosa - Abdul Rahman, Mohd Basyaruddin; Jumbri, Khairulazhar; Ng, Shie Ling; Basri, Mahiran; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar (2008)
Ionic liquids have open up new perspectives in catalysis and biocatalyst. Biocatalysis in nonaqueous media often face problems due to stability of enzyme which then lead to low activity and poor selectivity. Chiral ionic liquid coated-enzyme (CILCE) was prepared by coating Candida rugosa lipase with 1-hydrogen-3-hexylimidazolium hydrogen-tartrate. CILCE was later used to catalyse some non-chiral and chiral esterification of high value-added esters. CILCE was found to accelerate the production of short and medium chain esters with high percentage conversion compared to native lipase; dioleyl adipate 46%, oleyl hexanoate 44%, oleyl myristate 52% and oleyl palmitate 21%. For chiral esterification, CILCE has increased the percentage conversion upto 81% of (-)-menthyl butyrate.